2013
DOI: 10.1038/nature12361
|View full text |Cite
|
Sign up to set email alerts
|

PfSETvs methylation of histone H3K36 represses virulence genes in Plasmodium falciparum

Abstract: The variant antigen, Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1), expressed on the surface of P. falciparum infected Red Blood Cells (iRBCs) is a critical virulence factor for malaria1. Each parasite encodes 60 antigenically distinct var genes encoding PfEMP1s, but during infection the clonal parasite population expresses only one gene at a time before switching to the expression of a new variant antigen as an immune evasion mechanism to avoid the host’s antibody responses2,3. The mechanism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
370
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(390 citation statements)
references
References 36 publications
19
370
0
1
Order By: Relevance
“…4). Each parasite has the capacity to express about 60 different PfEMP1 molecules but usually only expresses one at a time (43)(44)(45). The data from experimental infections with a monoclonal parasite line indicate that among the hundreds of thousands of parasites that are released from the liver into the bloodstream, all PfEMP1 variants carried by the parasite are expressed (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…4). Each parasite has the capacity to express about 60 different PfEMP1 molecules but usually only expresses one at a time (43)(44)(45). The data from experimental infections with a monoclonal parasite line indicate that among the hundreds of thousands of parasites that are released from the liver into the bloodstream, all PfEMP1 variants carried by the parasite are expressed (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The most striking phenotypic difference revealed was the loss of transmission competence of KO and Trunc parasites, thus pointing to a functional role of PbZfp during mosquito stage development. Epigenetic mechanisms have been shown to play important roles in malaria parasite development, antigenic variation, Var gene silencing, and pathogenesis (43)(44)(45)(46)(47)(48)(49)(50)(51)(52). We found that trimethylation of H3K4, H3K27, and H3K36 was completely blocked in PbZfp KO parasites.…”
Section: Discussionmentioning
confidence: 49%
“…Modifications to histone H3 at the lysine 9 position (H3K9) appear to play a prominent role, with acetylation of this residue (H3K9ac) associated with the single active gene and trimethylation (H3K9me3) found at the silent remaining members of the family (73,74). In addition, trimethylation of the lysine at the 36 th position of the same histone (H3K36me3) is found at all var genes and has been shown to be important for maintaining mutually exclusive expression (75,76).…”
Section: The Potential Role Of Chromatin Structure In Var Gene Diversmentioning
confidence: 99%